PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR DALAM PEMBELAJARAN NORMA DALAM ADAT ISTIADAT DAERAHKU DI KELAS IV SD - Ahmad Fiqru Hidayat; Irwan Febryan; Made Sri Astika Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the quality of an interactive learning media in the form of an application on the topic of norms in local customs for fourth-grade elementary school students, viewed from the aspects of validity, practicality, and effectiveness. This research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 31 fourth-grade students at SD Negeri 1 Pengambengan. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests. The results showed that the developed interactive application has very good quality. In terms of validity, the application obtained a score of 90% from the material expert and 91% from the media expert, both categorized as highly valid, indicating that it is suitable for use in learning. In terms of practicality, the teacher response reached 92.5% and student responses reached 90.5%, both categorized as highly practical, indicating that the application is easy to use and engaging for students. In terms of effectiveness, there was an improvement in student learning outcomes, as shown by the increase in the average pre-test score from 64.28 to 86.07 in the post-test, with a gain of 21.79 points. Additionally, student learning mastery improved from 35% to 89%. The paired sample t-test result showed a significance value of 0.000 < 0.05, indicating a significant difference between learning outcomes before and after using the application. Therefore, the developed interactive application is proven to be highly valid, practical, and effective in improving student learning outcomes on the topic of norms in local customs.